Physical Hazards among Non-Healthcare Workers in Tertiary Hospitals in Rivers State - Etiobhio Etiobhio; Faith Ilosen; Onyeaso Onyeaso; Adedamola Olutoyin (Journal of World Science, 2025)
Non-healthcare workers in tertiary hospitals in Rivers State face a range of physical hazards, including slips, trips, and falls; eye strain; headaches; fatigue; and more severe injuries like cuts, bruises, fractures, electrical shocks, and body pains, particularly in the neck, shoulders, and back. Therefore, it is crucial to identify, assess, and control these hazards to improve workplace safety, reduce absenteeism, and enhance overall productivity. This study adopted a cross-sectional survey design. A self-structured questionnaire titled "Physical Hazards Questionnaire (PHQ)" with a reliability index of 0.89 was used for data collection. The data were collated, coded, and analyzed using the statistical package of social sciences (SPSS) version 25.0. The study's findings reveal that physical hazards among non-health care workers are a wide range of hazards that can compromise their health and safety. Age, gender, and years of work experience do not significantly influence the physical hazards faced by these workers. Age does not significantly predict physical hazards and gender does not create a significant difference in hazard exposure. The findings can guide interventions aimed at mitigating these hazards.